EVALUATION OF IN VITRO ANTIOXIDANT PROPERTIES OF TWO GARDEN EGG FRUIT CULTIVARS (Solanum aethiopicum F. and Solanum melongena F.) - C.,, UNEGBU CHIKA.; OBINNA, AJAH; E., NNAOMA IKENNA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Garden egg (Solanum melongena F. and Solanum aethiopicum F) is a plant native in india and Africa, and many cultivars exhibiting different size, shape and colour (white and green) are cultivated in tropical, subtropical, and temperate zones. This is ranked as one of the ten vegetables in term of oxygen radical scavenging capacity due to the presence of phenol, flavonoid, ascorbic acid and Beta carotene. 30g of the dried samples of garden egg (S. melongena and S.aethiopicum) were extracted with 20 volumes of 70% ethanol. The dried 70% ethanol samples were redissolved in methanol at different concentration. Samples B (S. melongena) is significantly higher in flavonoide content (72.97+10.75%), ascorbic acid content (72.97+1.4%) and b-carotene (5.388+0.6%) when compared with that of sample A(S. aethiopicum). the presence of these antioxidative parameters that were determined in garden egg extract proved its ability to inhibit free radicals which causes aging and damage to living tissues. The result of this research work revealed that extract of garden egg cultivars (S. melongena) is significantly higher in antioxidant properties than S. aethiopicum. Though both Garden egg can be utilizes as an effective and safe antioxidant source and ethanomedicine. So the cultivation and the eating of this fruit should be encouraged